The export strategy and SMEs employment resilience during slump periods - Daniel Aparicio-Pérez; Carolina Calatayud; María E. Rochina Barrachina (Economics: The Open-Access, Open-Assessment Journal, 2021)
The Spanish economy was the most hit by the Great Recession. It suffered a greater decrease in the gross domestic product (GDP) (affecting especially internal demand). However, it suffered a greater increase in exports (the so-called Spanish "miracle"). Particularly, Spanish SMEs incorporation into exports has been spectacular since 2008. Further, this has coincided with a huge increase in unemployment. Therefore, our main objective is to investigate the moderating role of exports in job destruction associated with recessive contexts of domestic demand using Spanish manufacturing SMEs as a case study. We obtain for SMEs that export participation helps compensate for the decrease in the number of workers generated by a (domestic) downturn, also increasing their survival. Otherwise, SMEs' survival is negatively affected by financial constraints, production costs, and a recessive demand. This compensatory effect of exports on employment works in favor of permanent workers, meaning that the ratio of permanent to temporary workers may increase for SMEs during recessive periods. Finally, we provide evidence that supports that participation of SMEs in exports is also due to a reaction to the fall in the domestic demand (the so-called "venting out" hypothesis) and, mainly, that this occurs for firms with high utilization of its productive capacity.
Keywords: E32; F14; M51; 330; exports; job losses due to domestic downturn; production capacity utilization; Spanish manufacturing SMEs; venting out